THE EFFECTIVETY OF CAROTENOID SPIRULINA PLATENSIS WHICH IS PRODUCED IN CULTURE MEDIA FROM KETCHUP WASTE AS AN ANTIOXIDANT - Sari, Luthfiana Aprilianita; Masithah, Endang D.; Alamsjah, Mochammad Amin (JFMR (Journal of Fisheries and Marine Research), 2018)
S. platensis is a health supplement as an antioxidant, sourced from carotenoid of S. platensis. Carotenoids can serve as singlet oxygen absorber and deactivate free radicals. The purpose of this study was to determine the effects of ketchup waste as organic fertilizer for the carotenoid of S. platensis. Also, to determine antioxidant activity (carotenoid) of S. platensis which is produced in culture media from ketchup waste compared to S. platensis commercial. The study consisted of two phases examination exploration of production time in order to obtain the highest value of carotenoid of S. pletensis and the effect of ketchup waste as an antioxidant (carotenoid) of S. pletensis by Difenil Pikril Hidrasil (DPPH). The results showed that carotenoid as an antioxidant S. platensis can produces carotenoid (1,5566 µg/mL) and antioxidant activity (DPPH 18,30%).